PEMBERDAYAAN KADER POSBINDU PTM DALAM UPAYA PENCEGAHAN PENYAKIT JANTUNG KORONER - Elmukhsinur, Elmukhsinur; Alice, Alice; Jannah, Fathul (PITIMAS: Journal of Community Engagement in Health, 2025)
Coronary Heart Disease (CHD) is the leading cause of death worldwide and in Indonesia. The incidence of cardiovascular disease continues to increase. PJK can be prevented by adopting a healthy lifestyle. The increase in cardiovascular disease (CVD) is due to the public's lack of knowledge about CVD risk factors, which leads to insufficient efforts by the public to prevent the disease. Preventing cardiovascular disease in the community is not only the responsibility of the government, but of all components within society, including community health workers. The role of cadres in organizing posyandu is very significant, not only as providers of health information but also as mobilizers of the community to attend posyandu. Thiscommunity service aims to increase cadres' knowledge and skills regarding the prevention of cardiovascular disease. The community service will be held from September 13th to October 25th, 2025, at the Pekan Heran Health Center. The implementation method began with a pretest of the cadres' knowledge about preventing cardiovascular disease (CVD), followed by practice and evaluation of the cadres' skills in educating about CVD, as well as practice and evaluation of their skills in measuring blood pressure and checking blood glucose and cholesterol. The data on the knowledge and skills of the cadres were statistically tested using the Paired sample T-test. The results of the statistical test for the knowledge and skills of the cadres showed a p-value of 0.000, meaning there was a significant improvement between the pretest and posttest scores of the cadres' knowledge and skills regarding the prevention of cardiovascular disease before and after the intervention.